A randomized study of pirarubicin (THP) versus adriamycin (ADM) for intravesical instillation therapy against superficial bladder cancer - Kawamura, J (Hinyokika kiyo. Acta urologica Japonica, 1992)
To determine the antitumor action by intravesical instillation prior to transurethral resection TUR, a randomized study on pirarubicin (THP) versus adriamycin (ADM) was performed for superficial, papillary and initially detected bladder cancers with participation of 21 Urological Clinics in 3 Tokai Prefectures. The instillation dose of 500 micrograms/ml was given 3 times per week for 3 weeks in both THP (n = 33) and ADM (n = 30) groups. The complete and partial response rates were 56.3% in THP group and 26.7% in ADM group. THP instillation was more effective against multiple tumors than a single tumor, stage Ta than T1 and grade G1 than G2 and G3. However, these findings were not statistically significant. Untoward effects were mainly bladder irritability and its frequency was 60.6% in the THP group and 23.3% in the ADM group. Contracted bladder was found in 2 of the 33 patients in the THP group and 2 of the 30 patients in the ADM group. The antitumor effect of a half dose of THP was equivalent to that of one dose of ADM, and the THP group showed a twofold higher frequency of side effects. Therefore, a clinical trial should be made comparing the effect of 500 micrograms/ml of THP and that of 1,000 micrograms/ml of ADM